Comparing effects of soybean oil- and palm olein-based mayonnaise consumption on the plasma lipid and lipoprotein profiles in human subjects: a double-blind randomized controlled trial with cross-over design. Issue 1 (December 2016) - Karupaiah, Tilakavati; Chuah, Khun-Aik; Chinna, Karuthan; Matsuoka, Ryosuke; Masuda, Yasunobu; Sundram, Kalyana; Sugano, Michihiro
Abstract Background Mayonnaise is used widely in contemporary human diet with widespread use as a salad dressing or spread on breads. Vegetable oils used in its formulation may be a rich source of ω-6 PUFAs and the higher-PUFA content of mayonnaise may be beneficial in mediating a hypocholesterolemic effect. This study, therefore, evaluated the functionality of mayonnaise on cardiometabolic risk within a regular human consumption scenario. Methods Subjects underwent a randomized double-blind crossover trial, consuming diets supplemented with 20 g/day of either soybean oil-based mayonnaise (SB-mayo) or palm olein-based mayonnaise (PO-mayo) for 4 weeks each with a 2-week wash-out period. The magnitude of changes for metabolic outcomes between dietary treatments was compared with PO-mayo serving as the control. The data was analyzed by ANCOVA using the GLM model. Analysis was adjusted for weight changes. Results Treatments resulted in significant reductions in TC (diff = −0.25 mmol/L;P =  0.001), LDL-C (diff = −0.17 mmol/L;P  = 0.016) and HDL-C (diff = −0.12 mmol/L;P  < 0.001) in SB-mayo compared to PO-mayo without affecting LDL-C:HDL-C ratio (P  > 0.05). Lipoprotein particle change was significant with large LDL particles increasing after PO-mayo (diff = +63.2 nmol/L;P  = 0.007) compared to SB-mayo but small LDL particles remained unaffected. Plasma glucose, apolipoproteins and oxidative stress markers remained unchanged. Conclusions Daily use with 20 g of linoleic acid-rich SB-mayo elicited reductions in TC and LDL-C concentrations without significantly changing LDL-C:HDL-C ratio or small LDL particle distributions compared to the PO-mayo diet. Trial registration This clinical trial was retrospectively registered with the National Medical Research Register, National Institute of Health, Ministry of Health Malaysia, (NMRR-15-40-24035; registered on 29/01/2015;https://www.nmrr.gov.my/fwbPage.jsp?fwbPageId=ResearchISRForm&fwbAction=Update&fwbStep=10&pk.researchID=24035&fwbVMenu=3&fwbResearchAction=Update ). Ethical approval was obtained from the National University of Malaysia's Medical Ethics Committee (UKM 1.5.3.5/244/SPP/NN-054-2011, approved on 25/05/2011).